2019
DOI: 10.1016/j.amjms.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Delayed Appropriate Antibiotic Therapy on Patient Outcomes by Antibiotic Resistance Status From Serious Gram-negative Bacterial Infections

Abstract: Background: To examine the clinical and economic burdens associated with delayed receipt of appropriate therapy among patients with Gram-negative bacteria (GNB) infections, stratified by antibiotic resistance status. Materials and Methods: Retrospective analysis using the Premier Hospital Database. Adult admissions (July 2011-September 2014) with evidence of complicated urinary tract infection, complicated intra-abdominal infection, hospital-associated pneumonia, or bloodstream infection, length of stay (LOS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 20 publications
2
75
1
2
Order By: Relevance
“…A rapid, simple and accurate detection method of pathogenic microorganisms was necessary for the timely administration of appropriate therapy and arriving at a time to discontinue unnecessary antibiotic(s). Delayed receipt of an appropriate antibiotic(s) was independently associated with poorer clinical and economic outcomes in patients with serious Gram-negative bacterial infections, regardless of any resistance status [9].Molecular diagnostic assays, such as PCR-based methods (e.g., conventional PCR, real-time PCR [17], and PCR-Electro Spray Ionization MS (PCR/ESI-MS) [18], permit more rapid detection of targeted bacterium by nucleic acid ampli cation, and have been established and applied in the clinic. However, these PCR-based techniques have some shortcomings, which include the following: (i) the instrument used is extremely expensive; (ii) the diagnostic speci city is highly affected by the ampli cation conditions and the primer design; (iii) use of these techniques indicate that PCR results require gel electrophoretic analysis or real-time analytical apparatus.…”
Section: Application Of Pa-mcda To Clinical Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…A rapid, simple and accurate detection method of pathogenic microorganisms was necessary for the timely administration of appropriate therapy and arriving at a time to discontinue unnecessary antibiotic(s). Delayed receipt of an appropriate antibiotic(s) was independently associated with poorer clinical and economic outcomes in patients with serious Gram-negative bacterial infections, regardless of any resistance status [9].Molecular diagnostic assays, such as PCR-based methods (e.g., conventional PCR, real-time PCR [17], and PCR-Electro Spray Ionization MS (PCR/ESI-MS) [18], permit more rapid detection of targeted bacterium by nucleic acid ampli cation, and have been established and applied in the clinic. However, these PCR-based techniques have some shortcomings, which include the following: (i) the instrument used is extremely expensive; (ii) the diagnostic speci city is highly affected by the ampli cation conditions and the primer design; (iii) use of these techniques indicate that PCR results require gel electrophoretic analysis or real-time analytical apparatus.…”
Section: Application Of Pa-mcda To Clinical Samplesmentioning
confidence: 99%
“…The conventional detection of P. aeruginosa in the clinical setting was generally achieved by growing the target pathogen on agar plate surfaces and cultures [8]. Although the culture-based technique is reliable, the time required for conducting it is at least for a period of 48 h [9]. Furthermore, published guidelines recommended an initial empiric combinatorial coverage with antibiotics targeted to Gram-negative and Gram-positive bacteria Methicillin-resisitant Staphylococcus aureus (MRSA) in the setting of high-risk VAP patients prior to obtaining culture results [1].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid application of effective antibiotics for bacterial infections can greatly decrease the length of hospitalization and risk of death . The rise of multidrug‐resistant bacteria, as well as the paucity of novel antibiotics, has led to many efforts to make the current arsenal more potent by combining older antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…With this information, physicians can make more informed empirical antibiotic selections, and thereby increase the likelihood of timely appropriate antibiotic therapy. Studies have shown that the critical window between infection onset and delivery of appropriate antibiotics is 48-72 h [17][18][19]. Our tool aids in antibiotic selection during this critical time window as Gram stain and rapid diagnostic test results become available within the first 12-24 h of culture collection.…”
Section: Introductionmentioning
confidence: 99%